One-step fabrication of two-dimensional hierarchical Mn2O3@graphene composite as high-performance anode materials for lithium ion batteries - Zhou, Zhou; Chaoying, Ding; Wenchao, Peng; Yang, Li; Fengbao, Zhang; Fan, Xiaobin (Journal of materials science & technology, 2021)
Two-dimensional (2D) hierarchical Mn2O3@graphene composite is synthesized by a one-step solid-phase reaction. The nanosheets of Mn2O3 are vertically grown on few-layered graphene, constructing a unique 2D hierarchical structure. As an anode material for lithium-ion batteries (LIBs), this hierarchical composite displays excellent electrochemical performances, showing an extraordinary reversible discharge capacity of 2125.9 mA h g–1. Moreover, a record high reversible capacity of 1746.8 mA h g–1 is maintained after 100 cycles at a current density of 100 mA g–1, which retains 82.2 % of the initial capacity. Such an outstanding performance could be attributed to its novel structure and the synergistic effects between the Mn2O3 and graphene.